THE ASSOCIATION OF BLOOD PRESSURE AND END-STAGE RENAL DISEASE IN ELDERLY DIABETES PATIENTS: A NATIONWIDE COHORT STUDY - Yu, Sung Hoon; Hong, Sangmo; Park, Jung Hwan; Kim, Dong Sun; Han, Kyungdo; Lee, Chang Beom (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION There is insufficient evidence to determine a precise blood pressure target in older adults with diabetes mellitus. In this study, we evaluated the potential relationship between blood pressure levels and end-stage renal disease (ESRD) in older diabetes patients without ESRD using a nationwide longitudinal population dataset from the National Health Information Database (NHID). METHODOLOGY We performed an observational retrospective cohort study including 267,156 older (≥65 years old) patients with diabetes and without ESRD from 2009 to 2018 based on the NHID. We divided the participants into eight groups based on their systolic blood pressure (SBP) and diastolic blood pressure (DBP). The primary composite outcome was ESRD. RESULTS During a median follow-up of 7.26 years, the incidence rate of ESRD was 2.03 per 1,000 person-years. In multivariable Cox proportional hazard modeling, the risk of the primary outcome was lowest in groups with an SBP of 100–119 mmHg and DBP of <80 mmHg. In a subgroup analysis according to the use of hypertension medication, there was a significant difference in DBP (p for interaction = 0.026) but no difference in SBP (p for interaction = 0.247). The risk of ESRD was the lowest in patients with an SBP of 110–129 mmHg taking hypertension medication and the highest in the group with an SBP of ≥160 mmHg. CONCLUSION Maintaining blood pressure at less than 120/80 mmHg might prevent progression to ESRD in older diabetes patients without cardiovascular disease.